Enhancement of Energy Dissipation by Using Different Shape of Baffle Block - A Review - Melan A.; Syamsir A.; Zawawi M.H. (Springer, 2023)
Energy dissipation is a crucial issue relating to the safety of the hydraulic structure. When water flows in high velocity, such structures have the harmful effect of converting the potential energy gained in the upstream side to kinetic energy in the downstream side. This energy must be dissipated shortly and safely as near as possible to the head structure to avoid its destructive effect. Baffle block is one of the efficient appurtenances that have a capacity in reducing the flow momentum that will decrease the flow velocity. Using baffle block is the main technique for accelerating the hydraulic jump formation and dissipating a great amount of the residual harmful kinetic energy occurring at the downstream of the spillway, channel or stilling basin. This paper reviews the experimental studies that have been done by previous researchers concerning the existence of the baffle block in the open channel and stilling basin. 2020, Springer Nature Singapore Pte Ltd.